Improvement of attention and episodic memory functions in community-dwelling older adults with cognitive impairment: A preliminary study using a multimodal method - Bunyachatakul, Saifon; Rattakorn, Phuanjai; Munkhetvit, Peeraya (Journal of Associated Medical Sciences, 2019)
Background: Global geriatric populations will result in increased rates of cognitive decline and dementia; elderly people may suffer from deterioration in cognitive ability, and particularly in attention and memory, that affects their functional independence. Thus, the combination methods of cognitive training are beneficial for enhancing their cognitive abilities and in slowing down the rise in numbers of demented elderly who live with cognitive impairment in the community. Objectives: To determine the effects of a multimodal episodic memory training (MEMT) protocol on attention and episodic memory performance in community-dwelling elderly with cognitive impairment. Materials and methods: Participants were the older adults living in community who are the members at the elderly school in the suburban municipal district, Chiang Mai province, Thailand. Twenty elderly with cognitive impairment were recruited through purposive sampling and assigned to the experimental group (n=10) and control (n=10). The experimental group received in a 36-sessions multimodal episodic memory training (MEMT) protocol including episodic memory training, multisensory stimulation, and mindfulness-based yoga training over 12 consecutive weeks. The attention and episodic memory scores were measured at baseline and after the intervention. Results: Participants receiving the MEMT protocol intervention demonstrated statically significant improvement (p<0.05) on attention and memory as compared with the control group, which showed no statically significant differences at the post-intervention. Conclusion: The findings of this study suggest that the 36 sessions within 12-week MEMT protocol intervention revealed the potential evidence in improving attention and memory in community-dwelling elderly with cognitive impairment.